Ta'lim Al-Ashwat Ála Dhaui Al-Ta'lim Al-Taáwuni ( Dirasah Al-Tajribiyah Fi Ma'had AlImarah Bandung) - Lina Marlina (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2018)
Cooperative learning is one of the learning models used by teachers in teaching and learning process, and it has many types when it is implemented in the classroom. In reality ashwat (Arabic phonology study) is one of the boring subjects considered by students in Ma'had Al-Imarot Bandung. The lecturer only instructs the students to pronounce the Arabic hijaiyyah letters and distinguish the letters adjacent to the makhraj (points of articulation of letters) and its nature. In the learning process, a lecturer uses only lecture method, who gives the examples of correct pronunciation then the students repeat those pronunciations after the lecturer. As a consequence, a lecturer should be able to update the learning process by using an interesting learning model by implementing cooperative learning for instance. The aims of this research is to know the reality of learning ashwat as Arabic pronunciation at Ma'had Al-Imarot Bandung, to know the ability of students to mastery of Arabic ashwat before applying cooperative learning in ashwat learning, to know the implementation of cooperative learning in ashwat learning, to know the advantages and disadvantages of cooperative learning in ashwat learning, as well as to know the students' ability to master Arabic ashwat after applying cooperative learning. This research is based on the framework that the implementation of cooperative learning in ashwat learning is effective. So the researcher states the hypothesis “cooperative learning is applied effectively in ashwat learning” The method used in this research is experimental method with quasi experimental design. There are two classes, namely the experimental class and the control class. The data collection techniques in this research are observation, interviews, and tests. the results find that the ability of students who mastering Arabic ashwat in the experimental class before applying cooperative learning showed good criteria with an average mark of 69.00 from pre-test. Surprisingly, the ability of students who mastering Arabic ashwat in the experimental class after applying cooperative learning showed excellent criteria with an average mark of 91.25 from post-test. After the researcher had tested the hypothesis, it can be concluded that cooperative learning was effectively applied in ashwat learning with the value of N-gain 0.68 which shows cooperative learning had improved students’ ability in Arabic ashwat about 68% with medium criteria.